Microneedles for controlled drug release - Ong, Jun Hao (2019)
With a growing pharmaceutical market each year, there are new methods for drug delivery to improve patient compliance. Hypodermic needles being commonly used when delivery biotherapeutics or vaccines. Patient complicane has decreased due to the pain experienced or having needle phobia. MN is one of the better alternatives to drug delivery. Out of the many different types of MN, hydrogel MN are studied as they have good biocompatibility, degradability and are nontoxic. In this paper, MeHA was chosen as the material to fabricate MN and were characterized. The different crosslinking duration were used to show how it affects the swelling ratio, loading of FITC on the MN as well as the rate of release of FITC. It was concluded that a lower crosslinking duration meant that it had a larger swelling ratio and was able to load more FITC. Release of FITC was faster in the lower crosslinking duration.